2017
DOI: 10.1007/s11682-017-9719-6
|View full text |Cite
|
Sign up to set email alerts
|

Repeated mild traumatic brain injuries is not associated with volumetric differences in former high school football players

Abstract: We investigated potential brain volumetric differences in a sample of former high school football players many years after these injuries. Forty community-dwelling males ages 40-65 who played high school football, but not college or professional sports, were recruited. The experimental group (n = 20) endorsed experiencing two or more mTBIs on an empirically validated mTBI assessment tool (median = 3, range = 2-15). The control group (n = 20) denied ever experiencing an mTBI. Participants completed a self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Several previous studies in both retired and active athletes have reported smaller hippocampal volumes associated with more exposure or repeated concussion (16,18,22,23). Other studies, however, have reported no associations (13,19,20), while a recent study observed larger hippocampal volumes in current athletes with prior concussion relative to matched athletes without a history of prior concussion (47). The current sample's distribution of concussion history (mean of 0.44 concussions) was considerably less than other prior studies recording an association between brain morphometry and concussion history.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several previous studies in both retired and active athletes have reported smaller hippocampal volumes associated with more exposure or repeated concussion (16,18,22,23). Other studies, however, have reported no associations (13,19,20), while a recent study observed larger hippocampal volumes in current athletes with prior concussion relative to matched athletes without a history of prior concussion (47). The current sample's distribution of concussion history (mean of 0.44 concussions) was considerably less than other prior studies recording an association between brain morphometry and concussion history.…”
Section: Discussionmentioning
confidence: 95%
“…( 11 16 , 22 , 24 26 ). Others, however, have also failed to record such a relationship or were unable to differentiate the effects of exposure and concussion ( 18 20 ). One possible explanation is that subcortical regions experience more mechanical stress from head impacts relative to the cortical mantle ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplications ( n = 146), 852 records were screened through identifying the titles and abstracts, and 24 records were retrieved for full-text reviews. Finally, a total of 11 studies [28,29,30,31,32,33,34,35,36,37,38] that met the inclusive criteria were included for this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in brain function and structure have also been shown in former American high school and college football players with cognitive deficits and depression, although these changes were not related to concussion history [ 44 ]. However, recent work from Terry and colleagues did not find a relationship between mild TBIs in high school football players and brain atrophy in later life [ 45 ].…”
mentioning
confidence: 99%